Empirical Analysis of the Risk-Return Characteristics of the Quoted Firms in the Nigerian Stock Market (Global Journal of Management and Business Research, 2011)
This study empirically investigates the risk-return dynamics of the Nigerian quoted firms for the period of 2000 - 2004 as monthly The objective of study is to establish what determines the systematic risk beta of firms the magnitude of such risk beta associated with returns in the Nigerian Stock Market This study employed Ordinary Least Squares OLS procedure to estimate the regression in order to obtain the systematic risk beta of each of the firm In addition market model was used to estimate returns of the firms This study revealed that the sizes of risks betas are different in firms studied they varied positively with the sizes of returns In addition 65 of the firms risk beta is statistically significant at 1 and 5 level and most of the firms risks betas are less than Unity which imply lower risk as compared to Market Portfolio More importantly most of firms betas are positive suggesting limited scope for diversification in the Nigerian Stock Market The outcome of this study conformed to similar studies in the emerging stock markets
Keywords: Risk-Return Characteristics; the Quoted Firms and the Nigerian Stock Market